Ideology and Symbolic Meaning: Critical Discourse Analysis of Gudang Garam International Filter Advertisement - Rameda, Naufal; Irwansyah (CARAKA : Indonesia Journal of Communication, 2024)
This research investigates how the Gudang Garam Filter Internasional cigarette ad, "The Greatest Choice," employs masculine rhetoric to shape consumer behavior and disseminate ideology. Utilizing Fairclough’s Critical Discourse Analysis (CDA) method, the study explores three critical dimensions: text, discourse practice, and socio-cultural practice. The descriptive analysis reveals the ad's emphasis on masculinity, depicting a man's character through hard work, success, and luxury. The interpretation of meaning in the advertising text creates a dualism of meaning, forming two interpretation perspectives: one from the cigarette enthusiasts and another from the product itself. In socio-cultural practice, this dualism reflects how perceptions are constructed in society, aiming to build the product's identity by embedding ideologies and values into Gudang Garam Internasional cigarettes. The study concludes the advertisement is not just a technology for promoting products, but also a means of spreading ideology. With the formation of the product’s image in society, it also becomes a tangible form that advertising has become an extension of human ability in persuasive communication.